Notary's Responsibility for Authentic Deeds Made With Forged Letter ( Case Study Decision No. 933 K/ Pid / 2023) - Rizka Saraswati Malinda; Budi Parmono; Sunardi (Dinasti Research, 2025)
Accountability Notary Public to deed authentic made with letter false often found that makes Notary Public face to face with problem law . article This use The approach method used in this study is the Normative Juridical approach method because the main data used is secondary data, namely data obtained based on literature studies, related regulations, and publications from related parties . The following are results analysis from writing article This namely , a Notarial Deed that has perfect evidentiary power, but if it violates certain provisions, its evidentiary value will be degraded to having evidentiary power as a private deed and can also be submitted through the cancellation of the notarial deed in court. False information that is the basis of a notarial deed does not make the deed null and void by law. Parties who feel disadvantaged by the deed are required to file a Civil lawsuit with the Court with the aim of canceling the deed that is detrimental to them. If the court has applied a permanent legal basis, then the deed is null and void by law.